Airborn / 1. - Oppel, Kenneth (Airborn, 2005)
Matt, a young cabin boy aboard an airship, and Kate, a wealthy young girl traveling with her chaperone, team up to search for the existence of mysterious winged creatures reportedly living hundreds of feet above the Earth's surface.